Outpatient initiation of the ketogenic diet in children with pharmacoresistant epilepsy: An effectiveness, safety and economic perspective. (September 2019) - van der Louw, Elles; Olieman, Joanne; Poley, Marten J.; Wesstein, Tessa; Vehmeijer, Florianne; Catsman-Berrevoets, Coriene; Neuteboom, Rinze
Abstract: Background: Children with pharmacoresistant epilepsy usually receive ketogenic diet (KD) as an inpatient, which makes it an expensive treatment. Objective: To compare the effectiveness, safety, and costs of outpatient versus inpatient initiated KD. Design: Retrospective observational non-inferiority study. Patients/setting: Patients (1–18 years of age) who started KD either inpatient or outpatient. Main outcome measures: Effectiveness was defined as ≥50% seizure reduction. Safety was measured by the numbers of emergency visits and complications. Economic impact was analyzed by calculating total costs of treatment. Statistical analyses: Non-inferiority of outpatient initiation was tested using 95% confidence intervals of the differences in effectiveness and safety endpoints between groups with non-inferiority margins of 10%. Nonparametric bootstrap techniques were used to derive a 95% confidence interval for the mean difference in total costs between the groups. Results: Hundred and five patients started KD in the period 2001 to 2017: 43 inpatient and 62 outpatient. At three months, the KD was effective in 61% of outpatients versus 63% of inpatients. The KD was considered safe in 36% of the outpatients, as compared to 29% in the inpatients. Outpatient initiation was shown to be non-inferior to inpatient initiation in terms of safety. Total health care costs of outpatient initiation were € 2901, as compared to € 8195 of inpatient initiation per patient (mean difference € 5294, 95% CI; -€ 7653 to -€ 2935). Conclusions: Our study suggests that outpatient KD initiation is no worse than inpatient initiation in terms of effectiveness and safety, while carrying lower health care costs. Highlights: Outpatient initiation of KD is as effective as inpatient KD initiation to reduce seizures. Outpatient initiation of KD is non-inferior to inpatient KD initiation in terms of safety. Outpatient initiation of KD is safe in children >1 year and/or no compromised medical condition. Outpatient initiation of KD reduces health care cost by reduction of costs of hospital admissions. Outpatient initiation requires a multidisciplinary approach.